Declining global fertility rates and the implications for family planning and family building: an IFFS consensus document based on a narrative review of the literature - Fauser, Bart C J M; Adamson, G David; Boivin, Jacky; Chambers, Georgina M; de Geyter, Christian; Dyer, Silke; Inhorn, Marcia C; Schmidt, Lone; Serour, Gamal I; Tarlatzis, Basil; Zegers-Hochschild, Fernando (Human reproduction update, 2024)
Abstract BACKGROUND Family-planning policies have focused on contraceptive approaches to avoid unintended pregnancies, postpone, or terminate pregnancies and mitigate population growth. These policies have contributed to significantly slowing world population growth. Presently, half the countries worldwide exhibit a fertility rate below replacement level. Not including the effects of migration, many countries are predicted to have a population decline of >50% from 2017 to 2100, causing demographic changes with profound societal implications. Policies that optimize chances to have a child when desired increase fertility rates and are gaining interest as a family-building method. Increasingly, countries have implemented child-friendly policies (mainly financial incentives in addition to public funding of fertility treatment in a limited number of countries) to mitigate decreasing national populations. However, the extent of public spending on child benefits varies greatly from country to country. To our knowledge, this International Federation of Fertility Societies (IFFS) consensus document represents the first attempt to describe major disparities in access to fertility care in the context of the global trend of decreasing growth in the world population, based on a narrative review of the existing literature. OBJECTIVE AND RATIONALE The concept of family building, the process by which individuals or couples create or expand their families, has been largely ignored in family-planning paradigms. Family building encompasses various methods and options for individuals or couples who wish to have children. It can involve biological means, such as natural conception, as well as ART, surrogacy, adoption, and foster care. Family-building acknowledges the diverse ways in which individuals or couples can create their desired family and reflects the understanding that there is no one-size-fits-all approach to building a family. Developing education programs for young adults to increase family-building awareness and prevent infertility is urgently needed. Recommendations are provided and important knowledge gaps identified to provide professionals, the public, and policymakers with a comprehensive understanding of the role of child-friendly policies. SEARCH METHODS A narrative review of the existing literature was performed by invited global leaders who themselves significantly contributed to this research field. Each section of the review was prepared by two to three experts, each of whom searched the published literature (PubMed) for peer reviewed full papers and reviews. Sections were discussed monthly by all authors and quarterly by the review board. The final document was prepared following discussions among all team members during a hybrid invitational meeting where full consensus was reached. OUTCOMES Major advances in fertility care have dramatically improved family-building opportunities since the 1990s. Although up to 10% of all children are born as a result of fertility care in some wealthy countries, there is great variation in access to care. The high cost to patients of infertility treatment renders it unaffordable for most. Preliminary studies point to the increasing contribution of fertility care to the global population and the associated economic benefits for society. WIDER IMPLICATIONS Fertility care has rarely been discussed in the context of a rapid decrease in world population growth. Soon, most countries will have an average number of children per woman far below the replacement level. While this may have a beneficial impact on the environment, underpopulation is of great concern in many countries. Although governments have implemented child-friendly policies, distinct discrepancies in access to fertility care remain. Graphical Abstract Declining fertility rates globally focus attention on the human right to build a family and the need for family-friendly policies and more accessible fertility care. LBGTQ, lesbian, gay, bisexual, transgender, queer, asexual, questioning.